The Rover Boys in the Jungle; Or, Stirring Adventures in Africa - Stratemeyer, Edward, 1862-1930 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Rover Boys in the Jungle; Or, Stirring Adventures in Africa" by Arthur M. Winfield (Edward Stratemeyer) is a novel written during the late 19th century. This story continues the adventures of the Rover Boys$1 (BDick, Tom, and Sam$1 (Bwho are young cadets set on a quest to find their father in the jungles of Africa. The plot revolves around their challenges and the many adventures they encounter in their search for Anderson Rover, who disappeared during an expedition years earlier. At the start of the novel, the Rover Boys return to Putnam Hall Military Academy, joyful to reunite with friends and resume their studies after a thrilling encounter on the ocean. However, the boys are soon met with unsettling news: their old enemy, Dan Baxter, has escaped from jail. This leads to a mix of concerns and determination among the brothers, reflecting their lingering battles with former adversaries. As they settle back into academy life, the arrival of new students and hints of further trouble arise, setting a tone of adventure and suspense that promises an exciting journey ahead as they eventually embark on their African expedition. (This is an automatically generated summary.)s
Release date is 2004-05-01
Produced by Sean Pobuda
Keywords: Adventure stories; Brothers -- Juvenile fiction; Africa -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Missing persons -- Juvenile fiction